Analysis of the transcriptome in molecular epidemiology studies. (1st August 2013) - McHale, Cliona M.; Zhang, Luoping; Thomas, Reuben; Smith, Martyn T.
<x xml:space="preserve">Abstract</x> The human transcriptome is complex, comprising multiple transcript types, mostly in the form of non‐coding RNA (ncRNA). The majority of ncRNA is of the long form (lncRNA, ≥ 200 bp), which plays an important role in gene regulation through multiple mechanisms including epigenetics, chromatin modification, control of transcription factor binding, and regulation of alternative splicing. Both mRNA and ncRNA exhibit additional variability in the form of alternative splicing and RNA editing. All aspects of the human transcriptome can potentially be dysregulated by environmental exposures. Next‐generation RNA sequencing (RNA‐Seq) is the best available methodology to measure this although it has limitations, including experimental bias. The third phase of the MicroArray Quality Control Consortium project (MAQC‐III), also called Sequencing Quality Control (SeQC), aims to address these limitations through standardization of experimental and bioinformatic methodologies. A limited number of toxicogenomic studies have been conducted to date using RNA‐Seq. This review describes the complexity of the human transcriptome, the application of transcriptomics by RNA‐Seq or microarray in molecular epidemiology studies, and limitations of these approaches including the type of cell or tissue analyzed, experimental variation, and confounding. By using good study designs with precise, individual exposure measurements, sufficient power and incorporation of phenotypic anchors, studies in human populations can identify biomarkers of exposure and/or early effect and elucidate mechanisms of action underlying associated diseases, even at low doses. Analysis of datasets at the pathway level can compensate for some of the limitations of RNA‐Seq and, as more datasets become available, will increasingly elucidate the exposure‐disease continuum. Environ. Mol. Mutagen. 54:500‐517, 2013. © 2013 Wiley Periodicals, Inc.